Precisely designing asymmetrical selenium-based dual-atom sites for efficient oxygen reduction - Xiaochen Wang; Ning Zhang; Huishan Shang; Haojie Duan; Zhiyi Sun; Lili Zhang; Yuanting Lei; Xuan Luo; Liang Zhang; Bing Zhang; Wenxing Chen (Nature Communications)
Abstract Owing to their synergistic interactions, dual-atom catalysts (DACs) with well-defined active sites are attracting increasing attention. However, more experimental research and theoretical investigations are needed to further construct explicit dual-atom sites and understand the synergy that facilitates multistep catalytic reactions. Herein, we precisely design a series of asymmetric selenium-based dual-atom catalysts that comprise heteronuclear SeN2–MN2 (M = Fe, Mn, Co, Ni, Cu, Mo, etc.) active sites for the efficient oxygen reduction reaction (ORR). Spectroscopic characterisation and theoretical calculations revealed that heteronuclear selenium atoms can efficiently polarise the charge distribution of other metal atoms through short-range regulation. In addition, compared with the Se or Fe single-atom sites, the SeFe dual-atom sites facilitate a reduction in the conversion energy barrier from *O to *OH via the coadsorption of *O intermediates. Among these designed selenium-based dual-atom catalysts, selenium-iron dual-atom catalysts achieves superior alkaline ORR performance, with a half-wave potential of 0.926 V vs. a reversible hydrogen electrode. In addition, the SeN2–FeN2-based Zn–air battery has a high specific capacity (764.8 mAh g−1) and a maximum power density (287.2 mW cm−2). This work may provide a good perspective for designing heteronuclear DACs to improve ORR efficiency.